Optimal location of capacitor bank for power losses minimization - Che Ros, Ziana (2013)
Power system consist of several components such are generations, transmission lines, distributions and loads. Each part consist of components that might encounter losses during their operations which then, can be divided into two categories: technical losses and non-technical losses. The main focus of this study is the technical losses that caused by the physical properties of components at transmission lines especially the MW loss and the Mvar loss. This thesis focused on the 9 Bus system analysis. Several studies have been conducted for this system which can be divided into two categories; The original setting ( stable system ) and the modified circuit for heavy loads setting where the loads capacity are increased to twice the value of the original setting. The purpose is to generate greater value of power losses. Thus, capacitor bank has been introduced to the system to minimize these losses. Several analysis have been done to determine the impact of installing the capacitor. Firstly, by varying the capacitor locations at all the busses in order to find the appropriate location of capacitor that might response to the power losses minimization the most. Record the MW losses and Mvar losses at each Busses and compare to the power losses of the original setting. This finally will show, which bus responses to the installed capacitor the most. Secondly, by varying the capacitor values installed at the effected bus in order to find the optimum range of the capacitor that will reduce Mvar losses the most. This Mvar range also can be calculated theoretically by applying an appropriate formula. The result is depending upon which capacitor value will decrease the power losses greatly. For acknowledgement, all the data and analysis are being done by the Powerworld Simulator Version 14 ( student version ). Finally, after completing all the analysis, the percentage of power losses reduction also can be determined theoretically . In fact, it can be concluded that many aspects to the capacitor compensation and its effects, depending on where capacitors get to be located, their sizes, and details of the distribution circuit.